STUDENT’S PERCEPTION ON MEMRISE APPLICATION TO IMPROVE VOCABULARY MASTERY AT SENIOR HIGH SCHOOL - Lia Rahman (JELLi Journal, 2022)
The purpose of this paper is to discuss some basic theories and previous research on student’s perception of memrise application to improve vocabulary mastery. A vocabulary is an essential tool for mastering all English skills. However, the fact shows that this part of the English language has been neglected, and due to inappropriate learning methods, it affects the students' lack of vocabulary, thereby exacerbating this phenomenon. To overcome this problem, online learning media is the most appropriate solution for students to learn vocabulary individually. Memrise is a learning media that is believed to help students learn English independently. Memrise is a mobile learning application that can expand students' vocabulary outside the classroom. In addition, Memrise is built into the educational application, so it will provide students with an enjoyable learning experience. Therefore, this paper explains vocabulary theory and types of vocabulary learning media here. Apart from that, this article will answer some questions about why students should use memrise and How do students apply the application. Previous research will be given in the next discussion to emphasize students' perceptions of the Memrise application. Then, this paper is expected to provide suggestions for English students to use good mobile-assisted language learning to expand their vocabulary.